Scale Participation of Parents and their Relationship on Schooling Students - Antonia Velez Tuarez, Maria; Rodriguez Gamez, Maria (International Journal of Psychosocial Rehabilitation, 2020)
The collaboration and interest that parents provide in the educational process of their children is vital to achieving a satisfactory school performance. The objective of the project was to verify the relationship between low parental participation and the academic performance of the students. For the writing of the article, a theoretical review of the literature was made and to obtain precise data the survey was used as an instrument. The results show that parents do not collaborate regularly on their children’s homework and school activities. Lack of time and parental interest affect more than their academic level in the school performance of students. Students not having control and supervision of parents spend little time to perform the tasks assigned. The assessment that students attribute to their school performance is similar to that provided by teachers.